2020
DOI: 10.1093/jac/dkaa219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risks factors associated with ESBL-producing faecal carriage in a single long-term-care facility in Spain: emergence of CTX-M-24- and CTX-M-27-producing Escherichia coli ST131-H30R

Abstract: Objectives To address the faecal carriage prevalence of antibiotic-multiresistant bacteria and associated risk factors in a public long-term care facility (LTCF). Methods A prospective study in a single government-funded LTCF of 300 residents in Ciudad Real, Spain. Residents’ clinical and demographic data were collected, as well as recent antibiotic consumption in the institution. Each participant contributed a rectal swab, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…These data indicated that the transmission of bla CTX-M-27 among E. coli isolates occurred via clonal expansion and horizontal transmission. The results of both clonal spread of resistant strains and horizontal transmission of the resistance plasmids contributed to the dissemination of bla CTX-M-27 -positive salmonella or E. coli isolates were also obtained in previous studies [16,17,39].…”
Section: Molecular Typing Analysissupporting
confidence: 59%
“…These data indicated that the transmission of bla CTX-M-27 among E. coli isolates occurred via clonal expansion and horizontal transmission. The results of both clonal spread of resistant strains and horizontal transmission of the resistance plasmids contributed to the dissemination of bla CTX-M-27 -positive salmonella or E. coli isolates were also obtained in previous studies [16,17,39].…”
Section: Molecular Typing Analysissupporting
confidence: 59%
“…The global spread of E. coli isolates producing bla CTX-M-27 was recently reported [ 40 ] . While these have been found in different parts of the world such as Germany, Spain, France, Japan, and China, they were not identified among the isolates analyzed in this study [ 10 , 35 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 70%
“…Population genomics on 4′071 global sources genomes observed a dominance of the clade C, co-circulating worldwide at stable frequencies [ 31 ]. In 2018, a single Spanish LTCF of 300 residents observed only 6 ST131 non-H30 associated with CTX-M-14 on 55 typed ESBL-EC isolates [ 32 ]. Our study observed that neither E. coli C2/H30-Rx, nor C1/H30-R, seem to drive the recent changing epidemiology of ESBL-EC in our LTCF, but rather a ST131 H89 harboring CTX-M-14 and CTX-M-27.…”
Section: Discussionmentioning
confidence: 99%